Gharar or Ghanimah? An Islamic Juridical (Fiqh) Analysis of Cryptocurrency (Bitcoin) as a Halal Asset in the Digital Economy - Ammar Al-Momani; Aigerim Tashbayeva; Nurgul Jumabekova (Islamic Studies in the World, 2025)
The rapid expansion of cryptocurrency, particularly Bitcoin, has generated intense debate within Islamic jurisprudence regarding its status as a halal or haram asset in the emerging digital economy. Contemporary Muslim scholars disagree on whether Bitcoin should be classified as gharar (excessive uncertainty) due to its volatility and speculative trading, or considered a new form of ghanimah (legitimate gain) enabled by technological innovation. This debate highlights a fundamental jurisprudential tension between classical fiqh principles and modern financial technologies, raising questions about how Islamic law should adapt to non-physical, decentralized digital assets. This study aims to provide a rigorous fiqh-based analysis of Bitcoin’s legal status by examining its characteristics in light of major Islamic legal maxims, classical texts, and contemporary fatwas. The research evaluates whether Bitcoin satisfies the criteria of mal (property), meets conditions of lawful trade (mu‘?mal?t), and avoids elements of gharar, maysir, and riba. The objective is to offer an evidence-based juridical assessment that can guide Muslim investors, regulators, and Islamic financial institutions. A qualitative juridical method was employed, combining textual analysis of classical fiqh literature, comparative evaluation of contemporary scholarly positions, and examination of economic data related to Bitcoin’s usage, volatility, and transactional patterns. These materials were analyzed using usul al-fiqh principles and the maqasid al-sharia framework. The findings indicate that Bitcoin can be considered halal under specific regulatory and transactional conditions, particularly when used as a medium of exchange or store of value rather than for speculative trading. The study concludes that Bitcoin’s permissibility depends on mitigating gharar and avoiding maysir through responsible usage, transparency, and adherence to sharia-compliant financial ethics.